Os novos paradigmas na política nacional de resíduos sólidos e os desafios do programa de coleta sustentável em João Pessoa - Soares, Rodrigo de Sousa (2014)
Study of the concepts, goals, deadlines and relevant instruments to Law 12.305 of 2010 that establishes the National Policy of Solid Waste ( PNRS ) in Brazil and its application, considering the challenges to consolidate a new reality of sustainable growth from the production of less waste, either in the manufacturing process or even in domestic consumption , extending the life cycle of products and allowing the country to definitely assume a sustainable development agenda. Assuming that the implementation of this Public Environmental Policy can mean the realization of new paradigms of development with sustainability as advocates Agenda 21, it has been sought beneath the perspective of economic law to highlight the legal implications from the concepts of the State of Social Welfare and Sustainable Development in Brazil. The legislation analysis indicates the importance of the principles of precaution and prevention within the framework of legal protection and the sharing of responsibilities in environmental management. Taking as parameter the management and implementation of PNRS in João Pessoa -PB and the experience in Brazil of selective collection with scavengers of recycled material. The local collection program and the challenges to have a sustainable collection program has been described, which facilitates the full operation of the reverse logistics and selective collection systems with social and economic inclusion of the scavengers of recycled material and the application of sectoral agreements and responsability pos - demand, causing a change in patterns of production and consumption .